Immune Checkpoint Inhibitor–Associated Sarcoidosis Reaction in the Kidney: Case Report - Mariam Charkviani; Sandra M. Herrmann (Kidney Medicine, 2023)
Sarcoid-like granulomas can be a manifestation of immune-related adverse events associated with immune checkpoint inhibitor (ICI) treatment. To our knowledge, kidney biopsy–proven sarcoid-like granulomas have not been described in the context of a sarcoid-like reaction associated with ICI treatment. We describe a man in his early 60s with renal cell carcinoma who was undergoing treatment with the ICIs nivolumab and ipilimumab, and was hospitalized for treatment of acute kidney injury stage 3, hypercalcemia, and hyponatremia 10 weeks after starting ICI treatment. Results from his workup showed parathyroid hormone–independent hypercalcemia (ionized calcium, 3.3 mEq/L) with an elevated 1,25-dihydroxyvitamin D level. A kidney biopsy specimen showed sarcoid-like noncaseating granulomas. The patient began a corticosteroid regimen with a 500 mg bolus dose of methylprednisolone and continued treatment with prednisone, 80 mg once daily for the first week and then a taper for 8 weeks. His kidney function gradually improved as hypercalcemia resolved. After 2 weeks of treatment, his creatinine values returned to baseline. This case shows that ICI treatment can be associated with kidney sarcoidosis. Because ICIs are increasingly used to treat cancer, physicians should be aware of this possible inflammatory complication so that they can use appropriate diagnostic and therapeutic approaches.